Students’ Motivation in Using Quizizz for Assessment - Ramadhani, Khori Putri; Chrismaretta, Chrismaretta (UICELL, 2023)
This research aims to analyze the level of students' motivation and the differences in motivation components between male and female students in the academic year 2021. The researcher used the questionnaire as the instrumentation. The researcher used totally sampling to choose the sample. The sample of this research consists of 96 students which are from English education and non-English education study program at Universitas Negeri Padang. In this study, the researcher use quantitative descriptive research as the research design. There were six subcomponents of motivation in this research i.e. intrinsic goal orientation, extrinsic goal orientation, task value, control of learning beliefs, self-efficacy for learning and performance, and task anxiety. The findings of the data analysis showed that students have high motivation levels. Females have a higher motivation level than males. It is shown by the mean score and the standard deviation. Keywords: motivation, quizizz, online assessment